Preparation Of Digital Learning Modules For Economics Lessons At Smas Ananda Batam - Cedrich Zakhariah; Hesniati Hesniati (ConCEPt - Conference on Community Engagement Project, 2023)
One of the senior high schools in Batam City named SMAS Ananda Batam has a problem in one of the steps of implementing the learning system. The problem lies in the use of student learning modules that are still analog or physical in nature such as textbooks, while technological developments are increasingly rapidly towards digital learning in this field of education. Therefore, the purpose of implementing this activity is to compile digital student learning modules in economics subjects so that they can help improve the quality of learning between students and teachers at SMAS Ananda Batam. The method of implementing this activity is observation and interviews in collecting data. The result of this activity is a digital learning module for economics students consisting of 2 e-modules on microeconomics for grade ten and 5 e-modules on macroeconomics for grade eleven. In addition, there are also recommendations or suggestions for this activity in the future, namely developing digital learning modules for economics lessons outside of microeconomics and macroeconomics, as well as other subjects as a whole so that Ananda Batam SMAS school can complement all of its student learning materials digitally in the future.